(untitled) (Raparin Journal of Humanities (RJH), 2019)
Leftism ideology came to Kurdistan through different ways like; social democracy movement, Iranian Communist Party, Iranian Tuddeh Party and invasion of Kurdistan by the red army and the support of the Soviet Union for the Kurdistan Republic. Since the leftism idea promoted justice and equality and removal of all kinds of oppression, it was attractive to the Kurdish intellectuals and so they welcomed it: the Kurdistan Revival association as the first nationalist party of Kurdistan (1942). In spite of this, it was a national-religious party, but the effect of left thoughts was clear. In that order they were against to the feudalism system as an socioeconomic regime of Kurdistan, and they tried to destroy tribal system in Kurdistan and at the same time they supported grubber class and specially farmer class. Kurdistan Revival Association to reach its main goal meaning creating a Kurdish Independent Government, was looking for foreign support, hence, its relations with the Soviet Union were very friendly and; even in its declarations, there are sympathize for socioeconomic system of Soviet Union.